Perception of tomorrow’s Health-Care connoisseur and front-runners of their educational environment utilizing DREEM inventory in Bahasa Melayu version, the native language of Malaysia - Mainul, Haque; Zulkifli, Zainal; Mohd Nasir, Farah Hanani; Majumder, Md. Anwarul Azim; Yusoff, Muhamad Saiful Bahri; Mostafa, Asma; Hoque, Rozina; Islam, Md. Zakirul; Myat Moe , Thwe Aung (Australasian Medical Journal, 2017)
Background There have been a lot of reports throughout the world that medical students were abused during their undergraduate education and clerkship training. Thereafter, calls for intensifying the evaluation of medical and health schools’ curricula based on students’ perceptions of their educational environment. Several studies, methods, and instruments were developed including the Dundee Ready Education Environment Measure (DREEM) inventory, to evaluate the medical educational environment in last five decades. The DREEM inventory has been translated into minimum eight different native tongues namely Arabic, Chinese, Japanese, Persian, Portuguese, Spanish, Swedish, and Turkish. Aims The objective of this study was to assess the educational environment of the UniSZA undergraduate medical program from the students’ perspective utilizing the DREEM inventory translated in Bahasa Melayu. Methods This was a descriptive cross-sectional survey conducted among the medical students of session 2015-2016 to assess educational environment of the Faculty of Medicine, UniSZA. The study was conducted from December 2015 to January 2016. Universal sampling technique was adopted. Results A total of 277 (95.5 per cent) out of 290 students responded to the questionnaire; among them 27.4 per cent were male and 72.6 per cent were female respondents. The overall mean DREEM scores for both preclinical and clinical students were 67.41±24.06. The scores for pre-clinical and clinical were 64.02±25.10 and 69.65±23.15 respectively; however, no statistically significant (p=0.57) differences was observed between two phases. A significant difference was observed between gender of the respondents in students’ perceptions of teachers (p=0.005) and students’ social self-perceptions (p=0.046).